2014
DOI: 10.3390/md12042036
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria from Terrestrial and Marine Sources Contain Apoptogens Able to Overcome Chemoresistance in Acute Myeloid Leukemia Cells

Abstract: In this study, we investigated forty cyanobacterial isolates from biofilms, gastropods, brackish water and symbiotic lichen habitats. Their aqueous and organic extracts were used to screen for apoptosis-inducing activity against acute myeloid leukemia cells. A total of 28 extracts showed cytotoxicity against rat acute myeloid leukemia (IPC-81) cells. The design of the screen made it possible to eliminate known toxins, such as microcystins and nodularin, or known metabolites with anti-leukemic activity, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 65 publications
2
28
0
Order By: Relevance
“…Interestingly, strain UC49.1 was highly toxic toward all cell lines in the organic extract, but produced no toxic substances in the aqueous extracts toward any of the cell lines. This demonstrates that the two obtained extracts, aqueous and organic, were different regarding the composition on Planctomycetes metabolites, similar to what has been demonstrated for cyanobacteria (Liu et al, 2014;Humisto et al, 2015). Still six strains showed activity in both extracts (>40%), which is likely to be caused by compounds with intermediate hydrophobicity present in both extracts.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, strain UC49.1 was highly toxic toward all cell lines in the organic extract, but produced no toxic substances in the aqueous extracts toward any of the cell lines. This demonstrates that the two obtained extracts, aqueous and organic, were different regarding the composition on Planctomycetes metabolites, similar to what has been demonstrated for cyanobacteria (Liu et al, 2014;Humisto et al, 2015). Still six strains showed activity in both extracts (>40%), which is likely to be caused by compounds with intermediate hydrophobicity present in both extracts.…”
Section: Discussionsupporting
confidence: 76%
“…The MOLM-13 cells were in general more sensitive toward the extracts compared to the PC cells (Figure 1). We have previously observed that the activity toward the MOLM-13 cells in the aqueous extracts can be due to high levels of adenosine (Prestegard et al, 2009;Liu et al, 2014). Adenosine has been shown to induce apoptosis in MOLM-13 cells (Tanaka et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria are photosynthetic prokaryotes, some of which are capable of using atmospheric N 2 as a nitrogen source. N 2 ‐fixing cyanobacteria are a prolific natural source of bioproducts (e.g., phicobiliproteins, carotenoids, fatty acids, and mycosporine‐like aminoacids) showing uncountable applications in the food and biomedical industries (e.g., neutraceuticals, food supplements, fluorescent tags, and UV‐screening compounds) and an enormous potential for the pharmaceutical industry due to the continuously growing number of bioactive compounds with anti‐cancer, anti‐viral, and anti‐bacterial activities discovered in cyanobacteria (Liu et al, ). To achieve a commercially profitable yield of those high‐value products, the selection of the appropriate photobioreactor (PBR) is crucial, with mixing time, volumetric gas transfer (O 2 , CO 2 ), and shear stress being the critical parameters to optimize PBR design.…”
Section: Productivity Of Anabaena Siamensis Biomass In Bubbled Suspenmentioning
confidence: 99%
“…In spite of recent improvement in therapeutic strategies, AML remains an incurable disease for majority of patients [30,32,33]. Predominantly, development of chemoresistance is a major bottleneck limiting the therapeutic efficacy in AML therapy [34]. Natural products are important source of anticancer lead molecule and have shown a promising anticancerous activity against various cancers [35,36].…”
Section: Discussionmentioning
confidence: 99%